Wearable Modular Telemetry System for the Integrated Rescue System Operational Use. (10th April 2017) - Kliment, Radim; Smrčka, Pavel; Hána, Karel; Schlenker, Jakub; Socha, Vladimír; Socha, Luboš; Kutílek, Patrik
Abstract : The article summarizes the development of the FlexiGuard modular telemetry system designed for enhancing safety of the Integrated Rescue System team members in solving crisis situations and for improving training processes. Further framework solutions, which lead to the development of automatic modular telemetry system allowing for real time monitoring of physiological parameters, are provided as well. The system provides for the signalization of critical states such as exhaustion, mental stress, and overheating. It further provides differentiation between the nature and intensity of movement, including actual and overall energy output, monitoring environmental parameters, and analysis of an intervention or training. The system has been tested in laboratories as well as in the terrain under real circumstances, and the eventual end users participated in its optimization process. Following the theory of games, a model of a transmission system was also created which demonstrates higher transmission efficiency when using higher number of nodes.